Rare Skin Diseases: Turban Tumor (Brooke-Spiegler Syndrome) - V. S. Dmitruk; V. G. Martynova; S. A. Khardikova; K. A. Skrylova; V. I. Shirshkova (Фундаментальная и клиническая медицина, 2024)
The Brooke-Spiegler syndrome is a rare autosomal dominant disorder characterized by development of multiple skin tumours including multiple cylindromas and trichoepitheliomas. Here we describe a case of 68-year-old man admitted at a consultative appointment into the surgical department of Siberian State Medical University with numerous asymptomatic, skin-coloured, dense smooth papulonodular lesions from 2 to 5 mm diameter over the face and with multiple pinkish dense smooth dome-shaped nodules from 1 to 5 cm over the scalp. The patient has noted their appearance since childhood. Earlier, similar lesions have been observed in his father and grandmother. Histopathological examination classified facial lesions as trichoepitheliomas and defined scalp lesions as cylindromas, thereby confirming the diagnosis of Brooke-Spiegler syndrome.